Impact of shearing on body weight and serum total proteins in ewes - Piccione, G.; Casella, S.; Alberghina, D.; Zumbo, A.; Pennisi, P. (Spanish Journal of Agricultural Research, 2010)
The aim of the present study was to evaluate the influence of shearing ewes during summer season on the evolution of body weight and serum total proteins. Forty Valle del Belice (Sicily, Italy) ewes, clinically healthy and well-fed, were divided into two groups of 20 subjects each. Twenty ewes were let unshorn as a control group (Group A) and 20 ewes were shorn (Group B). All animals were weighed using a mechanical balance in the morning before shearing and the measurements were repeated for each subject of Groups A and B after shearing (1 day) and after 7, 15, 30, 45, 60, 75 and 90 days from the shearing. In experimental days climatic conditions were recorded and temperature humidity index was calculated. Blood samples were collected by means of a jugular venipuncture and were centrifuged; and the obtained sera were separated to assess serum concentration of total proteins. Two-way repeated measures analysis of variance (ANOVA), followed by the Bonferroni’s test, was used to determine significant differences between two groups for body weight and total proteins. ANOVA did not show a significant effect of shearing and of time on body weight but showed a statistical significant effect of shearing and of time on total proteins. These confirm that shearing induces adaptive responses in the organism. Both shorn and unshorn ewes are subject to heat stress, but it is evident there is a different sensitivity to heat stress in shorn ewes in comparison with unshorn ewes.